1998
DOI: 10.2307/1132275
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Neighborhood and Family Income to Developmental Test Scores over the First Three Years of Life

Abstract: The effects of neighborhood and family income and family risk factors on developmental test scores at ages 1 through 3 are examined using a subsample (N = 347) from the Infant Health and Development Program. Beneficial effects of low numbers of risks were found for scores at ages 1 through 3. Family poverty was associated with lower scores at ages 2 and 3. Neighborhood affluence was associated with higher scores at age 3. The family risks-test score association at ages 1 through 3 and family income-test score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
3
7

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(118 citation statements)
references
References 0 publications
5
103
3
7
Order By: Relevance
“…In younger children (age 3), Klebanov, Brooks-Gunn, McCarton, and McCormick (1998) found that another proposed neighborhood process, availability of institutional resources (operationalized as learning experiences outside the home), did not mediate neighborhood effects on school readiness. However, learning experiences in the home, provided by parents, did mediate the relationship.…”
Section: Neighborhood Processes As Mediators Of Effectsmentioning
confidence: 89%
“…In younger children (age 3), Klebanov, Brooks-Gunn, McCarton, and McCormick (1998) found that another proposed neighborhood process, availability of institutional resources (operationalized as learning experiences outside the home), did not mediate neighborhood effects on school readiness. However, learning experiences in the home, provided by parents, did mediate the relationship.…”
Section: Neighborhood Processes As Mediators Of Effectsmentioning
confidence: 89%
“…The first is the Home Observation for Measurement of the Environment (HOME) scale, which has been widely used and consistently found to have important effects on children’s development (e.g., Bradley, 1995; Bradley et al, 1989; Klebanov et al, 1998). HOME scores are available for the NICHD-SECC sample at 6, 15, 36, and 54 months (scores are not available at 24 months or after 54 months).…”
Section: Methodsmentioning
confidence: 99%
“…Even after controlling for relevant personal and family background characteristics, residence in low income neighbourhoods has been shown to have negative effects on developmental outcomes in the first 4 to 5 years of children's lives and to be associated with higher rates of high school drop out and teen parenthood (Brooks-Gunn, Duncan & Aber, 1997). Additionally, neighbourhood income effects have been found to be smaller than the effects of family income, maternal education or maternal marital status (Klebanov, Brooks-Gunn, McCarton & McCormick 1998). …”
Section: Non-technical Summarymentioning
confidence: 99%